Human Behavior and the Social Environment II - Payne, Whitney (Open textbook library., 2020)
These materials will help students and instructors alike explore human behavior and how it is shaped and impacted by both traditional and non-traditional paradigms. This text will also support the reader in having a deeper understanding of how the environment, in all of its complexity, can affect individuals, families, groups, and communities. It is my hope that the information contained in this book will help you, as a future social worker, approach client systems with empathy, understanding, and a compassionate curiosity that allows for comprehensive assessment, individualized approaches to treatment, and continuity of care.